Transforming Rural Landscapes: Unleashing Agro-Tourism Potential Through Digital Media Interconnectivity - Khampusaen, Dararat; Naiyanit, Benjawan; Chanprasopchai, Thanya (Journal of Ecohumanism, 2024)
This study investigates digital media's collaborative potential and interconnectivity as public relations strategies aimed at enhancing agro-tourism in the Nong Kung Si District of Kalasin Province, Thailand. The study examined the interplay between digital media and agricultural tourism. The research evaluates how interconnected digital initiatives can effectively engage target audiences and improve tourist satisfaction. It utilized a mixed-methods approach where the data were collected through structured questionnaires to gauge perceptions of the online public relations efforts, assess the appropriateness of their components, and measure overall tourist satisfaction. Statistical analyses, including mean and standard deviation calculations, were employed to interpret the data. The findings highlight the critical role of interconnected digital media in promoting agro-tourism and identify best practices for fostering engagement and satisfaction among visitors. This research contributes to a deeper understanding of how collaborative communication strategies can drive sustainable tourism development in rural areas, emphasizing the importance of interconnectivity in enhancing agro-tourism potential.